Metode Pengukuran Tingkat Keluarga Sakinah Di Indonesia - Panjalu, Gandhung Fajar (Maqasid: Jurnal Studi Hukum Islam, 2023)
This study aims to explore a model for measuring the sakinah level of a family. The research method used in this research is library research. literature study is an activity related to the steps of collecting data by means of the library or based on existing data, reading and recording and processing research materials. The results of this study are the proposed form of the method used to measure the level of sakinah families in Indonesia based on the applicable laws and regulations. The results of this study indicate that there are 4 aspects that must be used to measure based on indicators from the Ministry of Religion regarding the Sakinah Family Movement, namely aspects of legality of marriage, spiritual aspects, physiological aspects and aspects of affection.